Capital Budgeting: Theory, Quantitative Methods, and Applications. - Wilkinson, Joseph W. (The Accounting Review, 1983)
Abstract Reviews the book "Capital Budgeting: Theory, Quantitative Methods, and Applications," by Anthony F. Herbst.